2023
DOI: 10.3389/fmed.2023.1115938
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 as a possible marker of neutrophilic asthma

Abstract: Asthma is a heterogeneous chronic disorder of the airways, with inflammation and bronchial hyperresponsiveness as its major underlying phenomena. Asthmatics vary in terms of inflammation pattern, concomitant pathologies, and factors aggravating the course of the disease. As a result, there is a need for sensitive and specific biomarkers that could facilitate diagnosing asthma as well as phenotyping in everyday practice. Chitinases and chitinase-like proteins (CLPs) seem promising in this field. Chitinases are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…[ 19 ] This study also found an association between elevated serum YKL-40 levels and 2 distinct asthma phenotypes: one characterized by irreversible airway obstruction and the other by severe exacerbation. [ 19 ] Building upon the cumulative evidence, Specjalski et al [ 18 ] also supported the notion that YKL-40 might predominantly represent non-T2 asthma. However, our investigation revealed that elevated serum YKL-40 levels were not effective in distinguishing between T2-high and T2-low asthma.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…[ 19 ] This study also found an association between elevated serum YKL-40 levels and 2 distinct asthma phenotypes: one characterized by irreversible airway obstruction and the other by severe exacerbation. [ 19 ] Building upon the cumulative evidence, Specjalski et al [ 18 ] also supported the notion that YKL-40 might predominantly represent non-T2 asthma. However, our investigation revealed that elevated serum YKL-40 levels were not effective in distinguishing between T2-high and T2-low asthma.…”
Section: Discussionmentioning
confidence: 94%
“…Despite the recent emphasis on investigating the relationship between YKL-40 and asthma, there remains a current lack of well-defined reference values for serum YKL-40, which could be used for asthma diagnosis or to distinguish its phenotypes and endotypes. Additionally, elevated serum YKL-40 levels have been observed in various conditions, including chronic obstructive pulmonary disease, tumors, and autoimmune diseases, [ 18 ] raising skepticism about its significance in asthma. Therefore, reevaluating the true value of YKL-40 in the context of asthma deserves careful consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation